COMMUNITY DYNAMICS OF MICROORGANISMS DURING CATTLE MANURE COMPOSTING PROCESS - Safika
Cattle manure, the waste product of cattle farm, nowadays has been used in small amount as fertilizer, biogas and compost. Manure composting process in Indonesia is generally carried out based on traditional method in which process a lot of nutrients has lost and the process itself takes a long time. Composting depends on the quality of organic materials, site of compost, composting methods, temperature, aeration systems, water content, C/N ratio and microorganisms that play role in the process. The unique cattle manure can be in good habitat for the communities of microorganisms degrading organic compounds. The understanding of community structure dynamics of microorganisms that play a role in the degradation of organic compounds in each composting phase is important to control the composting process effectively.